Efforts to Recover State Financial Losses through Asset Blocking as a Corruption Law Enforcement Strategy - Wijanarko, Dwi Seno; Wibowo, Cahyono (Budapest International Research and Critics University, 2021)
One of the elements in the criminal act of corruption is the loss of state finances. Against this state financial loss, the good old Corruption Law, namely Law no. 3 of 1971 and the newer Law no. 31 of 1999 in conjunction with Law no. 20 of 2001, stipulates a policy that state financial losses must be returned or replaced by perpetrators of corruption (Asset Recovery). The application of the law on state financial losses in relation to criminal acts of corruption that must be proven is the existence of state financial losses that have a causal relationship with the actions of the perpetrators of corruption. In this paper, the author uses a descriptive qualitative methodology to describe the conditions as they are, without giving treatment or manipulation to the variables studied.